How to write about the Holocaust : the postmodern theory of history in praxis - Pelekanidēs, Theodōros 1990- (Routledge approaches to history, 2022)
"How to write about the Holocaust is a contribution to ongoing debates in historiography and Holocaust studies. More specifically, it combines the theoretical framework that has developed in historiography in the last half a century with the demands of Holocaust representation. By analyzing major works about it, including Saul Friedländer's and Dan Stone's histories of the Holocaust, the book attempts to answer questions like: what is the most appropriate way to write about the Holocaust and what can theory teach us about the practice of history? To conclude, the volume explores the connection between history and literature and asks if the distinction between fact and fiction has become outdated"